Financial Aspects of Decentralized Planning in Kerala - Mini. M. Nair (ISDA Journal, 2013)
Decentralized economic planning has resulted in the financial devolution and empowerment of Local Self Governments (LSGs) in Kerala. As a result of financial empowerment LSGs are now capable of formulating programmes and plans to address the felt needs of local people. A sizable portion of the plan out lay of the state is now spent through LSGs. Provisions are made to spend on General Category, Special Component Plan and Tribal Sub Plan. Moreover total expenditure has to be made on the sectors such as production, infrastructure service and others. This paper looks into the Financial Aspects of Decentralized Planning focusing on grants - in - aid in Kerala,State Plan outlay and share of LSGs and category wise details of outlay of expenditure during the five year plans in different years from 1997 to 2012. Sector wise release of funds and its expenditure during the X and XI Plan are also examined.